Utilization of Cassava Rods Waste as Active Charcoal and The Effect of HCl Activator and Activation Time on Active Charcoal - Yuni Ambarwati; Nella P Syarifah; L Urip Widodo (UPN Veteran Jawa Timur, 2019)
Some research proved that activated carbon could be made from organic materials or anorganic material with very high carbon content. The exist research of activated carbon from coconut shell, bagasse, cassava peel. In fact, there are a lot of material can be used as raw material, like cassava rods wastebecause the amount is very abundant and has not been widely used. This research aims toreceive the right conditionsin the manufacture of activated charcoal from cassava stem wastewith variations in concentration and time of activationwith chemical activation methodsusing a hydrochloric acid activatorto obtain activated charcoal products that fulfill the standards. Making activated charcoal begins withdehydrate the stem in the sun for around 2 days. The second is make cassava charcoal by installing a series of clinker drum cassava stems. The third is charcoal stem activationwith the size 100 mesh, mix charcoal with Hydrochloric Acidinto erlenmeyerwith concentration 1,5N; 2N; 2,5N; 3N; and 3,5Nthen stir with Heating Magnetic Stirrer, 105 ºC, during 2,5 hours, 3 hours, 3,5 hours, 4 hours, 4,5 hours. The results obtained by the best active charcoalat concentration3 Nwith activation time 4,5 hours, ash content 0.8%, andabsorption of iodine 399,67 mg/g.